DBEA: A novel approach of repetitive data array compression for power system application - Sarkar, Subhra J.; Kundu, Palash K.; Sarkar, Gautam (2017 2nd International Conference for Convergence in Technology (I2CT), 2017)
Generally lossless compression techniques can give lower compression ratio. In this paper, an alternative scheme is tailored to compress generation scheduling information. It can reduce the data volume by 90% or even more for majority of the available scheduling data. While approaching towards the formation of smart grid, data management is extremely important. This low computational novel algorithm, DBEA can serve the purpose and can be embedded at microcontroller level to develop a smart autonomous system dealing with generation scheduling data. DBEA is developed and tested in C and MATLAB environment to obtain the results. The compression ratio achieved by the algorithm is promising and is comparable to the existing algorithm in other application domain. But the algorithm can be used for selected arrays only, particularly scheduling information array which is the limitation of the algorithm.